The effect of institutional and managerial ownership on tax avoidance: an empirical study of coal subsector mining companies listed on the Indonesian stock exchange for the 2017-2021 period - Malik, Dema Ilmi Annisa Amalliah; Rachmat, Radhi Abdul Halim (Universitas Wiralodra, 2023)
This study aims to determine whether institutional and managerial ownership affect tax avoidance in coal subsector mining companies listed on the Indonesian stock exchange. The factors tested in this study are institutional ownership and managerial ownership, while tax avoidance is the dependent variable. The research method used in this study is the explanatory method. The population in this study are coal mining companies listed on the Indonesian stock exchange. The sampling technique used in this study was purposive sampling with a total sample of 6 companies. The data analysis used in this research is panel data regression analysis. The program used to analyze the data is Eviews 12. Based on the study results, it can be concluded as follows: (1) the study results show that institutional ownership affects tax avoidance in companies in the coal mining sub-sector listed on the Indonesia Stock Exchange. (2) The study results show that managerial ownership affects tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange. (3) The study results show that institutional and managerial ownership affect tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange.